Endoscopic Treatment for Nonhypertrophic Idiopathic Pyloric Stenosis in an Adolescent Patient - Ferlini, Carlo Maria; De Lorenzi, Elena; Belgiovine, Cristina; Cereda, Emanuele; Caimmi, Silvia Maria Elena; Raffaele, Alessandro (European Journal of Pediatric Surgery Reports, 2023)
Nonhypertrophic idiopathic pyloric stenosis (NHIPS) is a rare occurrence in children. It could be related to peptic ulcers, but a definitive cause is yet to be found. Treatment is a matter of debate, ranging from medical to surgical. We report the case of a 15-year-old boy suffering postprandial vomiting and weight loss in the previous 3 months. NHIPS was diagnosed and successfully treated with several sessions of endoscopic pyloric dilation and jejunal feeding. In association with a multidisciplinary approach, endoscopic dilation should be considered as a first-line treatment to avoid surgery.
Keywords: nonhypertrophic; idiopathic; pyloric; stenosis; endoscopic; dilation; multidisciplinary approach